Rapid, two-pot procedure for the synthesis of dihydropyridinones; total synthesis of aza-goniothalamin - Cogswell, Thomas J.; Donald, Craig S.; Marquez, Rodolfo (Beilstein Journal of Organic Chemistry, 2020)
A fast, protecting-group-free synthesis of dihydropyridinones has been developed. Starting from commercially available aldehydes, a novel one-pot amidoallylation gave access to diene compounds in good yields. Ring-closing metathesis conditions were then employed to produce the target dihydropyridinones efficiently and in high yields.
Keywords: amidoallylation; aza-goniothalamin; dihydropyridinones; protecting-group-free; ring-closing metathesis; two-pot procedure